EDUKASI GEN Z KAYA LITERASI DINI - Wahnawidya Widhianingrum; Riawan Riawan; Ranti Kurniasih (Universitas Muhammadiyah Ponorogo, 2025)
Generation Z (Gen Z), who grew up in the digital era, has extensive access to information and technology. However, ironically, their financial literacy is still relatively low. 1 Based on data from the Financial Services Authority (OJK), the level of financial literacy among young people is still below 40%. 2 Therefore, more intensive efforts are needed to educate and improve financial literacy to help them manage their finances wisely. Through the